The Role of Teachers in the Development of Naturalis Intelligence in Science Learning - Djumat, Nurani; Purwanto, Agung; Akbar, Zarina (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to identify the teacher's role in developing naturalist intelligence in science learning at Yapis Kaimana Elementary School. This study uses a qualitative case study approach, with data collection techniques through observation, interviews, and documentation. Data were analyzed using Miles and Huberman analysis techniques, namely data reduction, data presentation, and conclusions. The primary data for this study were school teachers, students, grade 1 teachers, grade 3 teachers, grade 5 teachers, grade 6 teachers, and grade IV science teachers. The results of the study show that the teacher has a very important role in the development of naturalist intelligence in science learning at Yapis Kaimana Elementary School. Teachers use learning methods that focus on observation, experimentation, and hands-on experience to help students understand scientific concepts and build naturalist skills. In addition, teachers also provide opportunities for students to develop their interests and talents in natural sciences through activities such as environmental observations, school gardens, and simple research. This study shows that the teacher's role is very important in the development of naturalist intelligence in science learning at Yapis Kaimana Elementary School. In developing naturalist intelligence, teachers must be able to identify the needs and interests of students and choose appropriate learning methods. In addition, teachers must also help students develop naturalist skills through activities that are relevant to their context and environment. This research can be a reference for teachers and schools in developing science learning that is effective and oriented towards developing students' naturalist intelligence.